PENINGKATAN KAPASITAS UMKM DESA SUMBER MULYO MELALUI STRATEGI DIGITAL MARKETING - Yopita, Yopita; Pratama, Reza Hardian (MAJU : Indonesian Journal of Community Empowerment, 2025)
Micro, Small, and Medium Enterprises (MSMEs) play a significant role in supporting rural economic growth, including in Sumber Mulyo Village, Tanggamus Regency. However, product marketing challenges remain one of the primary obstacles faced by MSME actors. This community service program aims to enhance the capacity of MSMEs through training and mentoring on digital marketing strategies. The program includes education on utilizing social media, online marketplaces, and creating engaging content to attract consumer interest. The methods used in this program involve theoretical training, practical simulations, and direct mentoring in designing and executing digital marketing campaigns. The expected outcomes are improved understanding among MSME actors regarding digital marketing strategies, enhanced skills in creating attractive marketing content, and increased capability to leverage digital platforms for broader market reach. With this capacity enhancement, MSMEs in Sumber Mulyo Village are expected to become more competitive in marketing their products online, thereby supporting sustainable and technology-based rural economic growth.